If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 2 = 3x + -5 Reorder the terms: 2 + 2x = 3x + -5 Reorder the terms: 2 + 2x = -5 + 3x Solving 2 + 2x = -5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 2x + -3x = -5 + 3x + -3x Combine like terms: 2x + -3x = -1x 2 + -1x = -5 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -1x = -5 + 0 2 + -1x = -5 Add '-2' to each side of the equation. 2 + -2 + -1x = -5 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -5 + -2 -1x = -5 + -2 Combine like terms: -5 + -2 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 3r-3c-3r=2r | | -32=X+3 | | 3(2x+1)-4x= | | 7x+9=2x+124 | | 0.4x+8=0.6x-8 | | 7x-8=3x+5 | | 7x+4=3x-8 | | X-7=39 | | 10w+99=189 | | 9y+45=-1y+135 | | 2x+3(4-2x)=2(x+3) | | 4x+3(40-x)=125 | | 4-7x=4x+13 | | 3x^3-12x^2+16x-8=0 | | 5v+2v-v+3w= | | -8t=-72 | | 3x+6=-3(-1-x) | | 4x=3x+2x-5 | | 5z-4=3(z+2)+2z | | 3x+5x=2x+2 | | 3x+5x=2x | | 14+.6p=8 | | 2k-10=6 | | (5)(n)(6)=60 | | 2+3x-12-2x=4x+1 | | 60+3x=200-2x | | 14+.67p=8 | | 4(x-2)=-3(x+19) | | 7(y+5)=9y+19 | | 7(x+5)=9y+19 | | (-13)=n+9 | | 8x+4-2x=3(2x+2)-2 |